THE EFFECT OF ORGANIZATIONAL CULTURE, QUALITY OF HUMAN RESOURCES, AND THE MOTIVATION TO THE EMPLOYEES PERFORMANCE IN THE CORRECTIONAL INSTITUTION CLASS IIA OF BATAM WITH THE WORK DISCIPLINE OF INTERVENING - Handoko Gotama, William; Satriawan, Bambang; Indrayani, Indrayani; Khaddafi, Muammar (RADJA PUBLIKA, 2022)
The purpose of this research is to analyse the influence of organizational culture variables, human resource quality and performance motivation against work discipline as a intervening variable. The research object was conducted at the Correctional Institution class IIA of Batam City. The purpose of this research is to know the influence of organizational culture to employee performance, influence of human resource quality to employee performance, influence of work discipline on employee performance, organizational culture influence, human resource quality and motivation to employee performance through work discipline, as well as knowing greater where direct influence than indirect influence between organizational culture to performance through work discipline, quality of human resources to performance through working discipline and motivation to performance through work discipline. Respondents in this study amounted to 30 employees and the analytical models used in this study were descriptive analysis, and multiple linear regression analyses with the SPSS for Windows 20.0 program. The results of this study show that organizational culture has a positive and significant influence on employee work discipline. The quality of human resources has a positive and insignificant effect on employee work discipline. Motivation has a negative and insignificant effect on employee work discipline. Organizational culture has a positive and significant effect on employee performance. The quality of human resources has a negative and insignificant effect on employee performance. Human motivation has a positive and insignificant effect on employee performance. Work discipline has a negative and insignificant effect on employee performance.